Potato-fiber modified thermoplastic starch: Effects of fiber content on material properties and compound characteristics. (February 2019) - Fahrngruber, Barbara; Eichelter, Johanna; Erhäusl, Sabine; Seidl, Bernhard; Wimmer, Rupert; Mundigler, Norbert
Graphical abstract: Highlights: Sustainable potato fiber, a biorefinery by-product, as green additive in TPS. Overall characterization of TPS and fiber modified TPS (Microscopy, SEC, XRD, FTIR, DMTA). The fiber additive interacts with thermoplastic starch to form an amorphous, hydrophilic network. Structure-property relationship in TPS has an effect on compound and film characteristics. Film material with haptic and mechanical properties suitable for industrial applications. Abstract: The implementation of bio-based additives in polymer formulations provides possibilities to tailor material characteristics for more sustainable solutions. Fibers derived from natural sources and of sustainable origin have been gaining importance for bio-based as well as biodegradable packaging, showing also high performance. In this research, potato-fiber modified thermoplastic starch (TPS, fiber contents 1, 3 and 5 wt%) was prepared, which was used in the subsequent production of TPS/polyester compounds. Characterization results revealed a reduced formation of closely-packed crystalline structures in TPS, along with increasing fiber content. Likewise, an increase in materials rigidity was observed, as determined via dynamic mechanical analysis. Within the compounded material, potato-fiber additions enhanced a molecular weight reduction in starch while the formation of agglomerates was induced. The prepared films exhibited increased mechanical stiffness and also modified sorption characteristics. The identified property profiles are instrumental in creating novel, custom-tailored packaging materials.